2022
DOI: 10.1055/s-0042-1759522
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on PCOS among the Nursing Students of a Selected College, Mangaluru

Abstract: Polycystic ovarian syndrome (PCOS) is an endocrine disorder commonly affecting the adolescent girls. Globally, the prevalence rate is around 4 to 12% and it affects 5 to 10% women in their reproductive age group. The study was conducted to assess the knowledge on PCOS among the student nurses. This was a questionnaire-based cross-sectional study among 350 adolescent girls of a selected nursing college recruited using stratified random sampling. A predesigned, pretested, semistructured 16-item questionnaire con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Several studies [51,64] have revealed that the majority of nursing students had ample knowledge of PCOS, but awareness of PCOS was poor. The studies also suggested an urgent need for increasing awareness about PCOS to prevent its long-term consequences.…”
Section: Knowledge and Awareness Of Pcosmentioning
confidence: 99%
“…Several studies [51,64] have revealed that the majority of nursing students had ample knowledge of PCOS, but awareness of PCOS was poor. The studies also suggested an urgent need for increasing awareness about PCOS to prevent its long-term consequences.…”
Section: Knowledge and Awareness Of Pcosmentioning
confidence: 99%